Carbono da biomassa microbiana e nas frações húmicas do solo sob diferentes sistemas de uso e manejo no cerrado mineiro - Nayara Christina Almeida Araújo (2016)
The Integrated agricultural production systems are seen as viable alternatives to sustainable land use. This work aimed to evaluate the microbiological attributes and the humic fractions of soil organic matter in areas submitted to different systems of land use and management in the city of Curvelo - MG. This work was conducted at Fazenda Experimental do Moura da Universidade Federal dos Vales Jequitinhonha e Mucuri, UFVJM (Experimental Farm of Moura, Federal University of Jequitinhonha and Mucuri Valleys - UFVJM), located in the city of Curvelo, in the State of Minas Gerais. Seven systems of use were selected: three crop-livestock-forest integration systems, with crop variations among Eucalyptus urograndis, maize, marandu grass and java; Monocultures of java (JAVA) and marandu grass (MAR); consortium between java and maradu grass (J + M) and low productivity pasture (PAST). The soil samples were collected in winter (July 2015) and summer (January 2016) at three depths to determine microbial biomass carbon (C-BMS), basal respiration (C-CO2), and the microbial metabolic quocient of soil. For the fractionation of SHs in humic fraction (HUM), humic acid fraction (FAH) and fulvic acid fraction (FAF), samples were collected only in summer (January 2016) at the three depths. The FAH / FAF ratio and the relation between the alkaline extract (FAF + FAH) and the HUM (EA / HUM) were calculated. Soil microbiological attributes were more influenced by the time of year than by the management systems. The carbon in the microbial biomass varied between 79 and 598 mg kg-1 of soil and the microbial quotient between 0.40 and 2.84%, being these values higher in the rainy period. The metabolic quotient ranged from 0.18 to 2.03 and was lower in the same period, indicating that the microorganisms spent less energy by using the available substrate, incorporating more C to their biomass. The basal respiration of the soil did not differ for the two seasons, with the exception of the MAR that presented smaller averages for the dry period. In the dry period, for the depth of 5-10 cm, the ILPF-J presented a C-BMS value of 222 mg kg-1 of soil superior to those found in monocultures and in PAST. The highest values of TOC and NT and C of the humic fractions were found in the VN. The FAF decreased in deeper layers of the soil, mainly in the VN, being a very soluble fraction in the soil. The values of FAH / FAF ratio above 1.0 showed the predominance of FAH fraction in relation to FAF, a result attributed to intense humification of MOS. The HUM fraction was higher than the other fractions in all evaluated depths, and the low values of the EA / HUM ratio indicate higher recalcitrance of the MOS in the evaluated systems. The ILPF-M system presented an increase in NT and C-HUM content in relation to PAST, and these results are related to the degree of degradation that the pasture is, contributing with less amount of plant material to the soil. As the VN is an environment in dynamic equilibrium, the environment presented better soil quality (QS) when compared to the other treatments. However, the integrated production systems (ILPF and ILP) presented improvements in QS in relation to low yield pasture and may be indicated for the recovery of degraded soils.